Composite indicators for computer-aided collective bargaining - Andranick S. Tanguiane (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2019)
A negotiation model for flexicurity-relevant collective bargaining is developed. It is based on the Dutch computer archive of about 5,400 collective agreements called in the Dutch literature collective labor agreement (CLA). First, the opposite interests of negotiating sides are specified - a list of security items from the trade union side and a list of flexibility items from the employers' side. These items are quantified using some indices; then two composite indicators - for security and flexibility - are defined. A perfect parity agreement should have 0-balance, by analogy with credit-debit 0-balance in finances. Since the flexibility and security indices are expressed in different scales ("in different currencies"), the substitution rate ("exchange rate") is determined by regression analysis of flexicurity-relevant agreements from the past practices, finding how (on the average) flexibility is compensated by security.
Keywords: 330